Pelatihan Bahasa Inggris Pemasaran Produk Non-Kayu untuk Meningkatkan Sumber Daya Manusia di Hutan Pendidikan, Kabupaten Malang - Asihing Kustanti; Rizkiana Maharddhika; Hafida Ruminar; Dian Islami Prasetyaningrum (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
Community service carried out by a team of English lecturers at UB Forest Malang aims to improve the ability of UB Forest Malang staff in conducting marketing communications for UB Forest's Non-Timber Forest Products in English. The duration of this community service is approximately three months, covering drafting of training materials, intensive English communication training, as well as assistance in making activity outputs, namely video presentations on marketing UB Forest products in English by participants. The form of community service carried out is English language training which is focused on marketing communication activities in English that are tailored to the needs of UB Forest staff. In this training, around 20 UB forest staff practice being marketing staff by presenting non-timber products owned by UB Forest in English.